PENDAMPINGAN PENYUSUNAN SOAL BERKATEGORI HOTS BAGI GURU MADRASAH ALIYAH MU’ALLIMIN MU’ALLIMAT REMBANG - Mohammad Agus Prayitno; Dian Tauhidah Tauhidah (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
Curriculum changes require students to be able to think at higher levels. For this reason, educators are expected to be able to compile HOTS categorized questions that their students will give in each evaluation. The results of the field study obtained information that the socialization of HOTS categorization of questions was needed to the madrasah teachers. The purpose of implementing this Community Service Program (PKM) is to inform teachers to understand HOTS question categories, and to arrange HOTS categorized questions based on the preparation steps. The PKM was conducted at MA M3R with the method of presentation, question and answer, and demonstration. The material presented at the time of socialization are: a) cognitive level theory, b) LOTS and HOTS explanations, and c) steps for preparing HOTS questions. The results showed that the participants' responses to the socialization were very good, which was shown actively during the question and answer session, as well as a positive change in understanding in understanding the HOTS category before and after the socialization. The conclusion is the socialization of making HOTS categorized questions can provide information to participants of the socialization in identifying HOTS questions as well as the steps in preparing HOTS questions.